Bird's Eye View of a Neonatologist: Clinical Approach to Emergency Neonatal Infection - Fu-Kuei Huang; Hsiu-Lin Chen; Peng-Hong Yang; Hung-Chih Lin (Pediatrics and Neonatology)
Though the incidence of neonatal infection in term and near-term infants is relatively low, incidence of infection in preterm very low birth weight infants is as high as 20–30% and may result in neurodevelopmental impairment or mortality. Pediatricians should be familiar with recognition and emergency management of life-threatening neonatal infections, such as congenital pneumonia, early onset sepsis, late onset sepsis, bacterial and fungal meningitis, disseminated neonatal herpes simplex virus (HSV), and HSV meningoencephalitis. For the pediatrician, it is logical to approach the management of these infections by time of onset, i.e., early versus late onset of infection. Perinatal risk factors and simple laboratory tests, such as total white blood-cell count, immature/total ratio, and C-reactive protein are helpful in guiding the decision of antibiotics therapy. Successful management of these critical infections depends upon early diagnosis and timely administration of adequate antibiotics. Empiric antibiotic therapy must cover the most likely pathogens according to the risk factors of each individual neonate, and therapy duration is dependent upon culture results, clinical course, and the microorganism. Future research may focus on developing a practical neonatal sepsis score system based on risk factors and common biomarkers, which are readily available at bedside to make early accurate decisions and achieve better outcomes.